Aku Bersyukur, Aku Bahagia: Program Intervensi Psikologi Positif Berbasis Experiential Learning Untuk Meningkatkan Kebersyukuran Pada Siswa Sekolah Dasar - Fahwan Aldi Pratama; Farah Syahla Dzahabiyah; Najwa Salvabillah Putri Rahdiansyah; Samuel Naufal Rahmat Yefta Tuwaidan; Lenny Utami Afriyenti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Gratitude is a positive character strength that plays an important role in children's social, emotional, and psychological development. However, cultivating gratitude cannot be achieved solely through lectures or advice. This study aimed to examine the effectiveness of an Experiential Learning–based positive psychology intervention program entitled